A Comparative Analysis of the Flow Properties between Two Alumina-Based Dry Powders - Milene Minniti de Campos; Maria do Carmo Ferreira (Advances in Materials Science and Engineering)
We measured and compared the flow properties of two alumina-based powders. The alumina powder (AP) is irregularly shaped and has a smooth surface and moisture content of 0.16% (d.b.), and the ceramic powder (CP), obtained after atomization in a spray dryer, is spherical and has a rough surface and moisture content of 1.07%. We measured the Hausner ratio (HR), the static angle of repose (AoR), the flow index (FI), the angle of internal friction, and the wall's friction angle. The properties measured using aerated techniques (AoR and HR) demonstrated that AP presents true cohesiveness (and therefore a difficult flow), while CP presents some cohesiveness and its flow might be classified as half way between difficult and easy flow. Their FI values, which were obtained using a nonaerated technique, enable us to classify the alumina as cohesive and the ceramic powder as an easy-flow powder. The large mean diameter and morphological characteristics of CP reduce interparticle forces and improve flowability, in spite of the higher moisture content of their granules. The angles of internal friction and of wall friction were not significantly different when comparing the two powders.